Mycorrhizal Switching and the Role of Fungal Abundance in Seed Germination in a Fully Mycoheterotrophic Orchid, Gastrodia confusoides - Li, Yuan-Yuan; Boeraeve, Margaux; Cho, Yu-Hsiu; Jacquemyn, Hans; Lee, Yung-I (Frontiers in Plant Science, 2022)
Mycorrhizal associations are essential for orchid germination and seedling establishment, and thus may constrain the distribution and abundance of orchids under natural conditions. Previous studies have shown that germination and seedling establishment in several orchids often decline with increasing distance from adult plants, resulting in nonrandom spatial patterns of seedling establishment. In contrast, individuals of the fully mycoheterotrophic orchid Gastrodia confusoides often tend to have random aboveground spatial patterns of distribution within bamboo forests. Since G. confusoides is parasitic on litter-decaying fungi, its random spatial patterns of distribution may be due to highly scattered patterns of litter-decaying fungi within bamboo forests. To test this hypothesis, we first identified the main mycorrhizal fungi associating with developing seeds and adult plants at a bamboo forest site in Taiwan using Miseq high-throughput DNA sequencing. Next, we combined seed germination experiments with quantitative PCR (qPCR) analyses to investigate to what extent the abundance of mycorrhizal fungi affected spatial patterns of seed germination. Our results show that seed germination and subsequent growth to an adult stage in G. confusoides required a distinct switch in mycorrhizal partners, in which protocorms associated with a single Mycena OTU, while adults mainly associated with an OTU from the genus Gymnopus. A strong, positive relationship was observed between germination and Mycena abundance in the litter, but not between germination and Gymnopus abundance. Fungal abundance was not significantly related to the distance from the adult plants, and consequently germination was also not significantly related to the distance from adult plants. Our results provide the first evidence that the abundance of litter-decaying fungi varies randomly within the bamboo forest and independently from G. confusoides adults.